Case Report: A Novel Mutation Leading to 11-β Hydroxylase Deficiency in a Female Patient - Ozbas, Burak; Demir, Mikail; Dursun, Huseyin; Sahin, Izem; Hacioglu, Aysa; Karaca, Zuleyha; Dundar, Munis; Unluhizarci, Kursad (Endocrine, Metabolic & Immune Disorders-Drug Targets, 2023)
Background: 11β hydroxylase deficiency (11βOHD) ranks as the second most common enzyme deficiency that causes congenital adrenal hyperplasia. Depending on the severity of the enzyme deficiency, it can lead to cortisol deficiency, androgen excess and hypertension due to increased mineralocorticoid precursor levels. Many different types of mutations in the CYP11B1 gene located on chromosome 8q24.3 have been shown to cause 11βOHD. Here, we report a novel missense mutation that leads to 11βOHD in a female patient. Case Presentation: A 35-year-old female patient was admitted to the Endocrinology Department with a complaint of abdominal pain. The patient had a history of genital reconstruction surgery twice in childhood. On physical examination, an abdominal mass was detected. Laboratory examination of the patient revealed low levels of cortisol, potassium and high levels of ACTH, 11-deoxycortisol and androstenedione, suggesting 11βOHD. Genotyping showed a novel homozygous missense mutation (c.1385T>C L462P variant) detected on the 8th chromosome where the CYP11B1 gene is located. Glucocorticoid therapy was commenced for the patient whose diagnosis of 11βOHD was confirmed by both hormonal and genetic tests. A mass originating from the left adrenal gland with the largest diameter of 7 cm was compatible with myelolipoma. Conclusion: In this case report, we aimed to contribute to the literature by reporting a new missense mutation in the CYP11B1 gene, leading to classic type 11βOHD that has not been described before.
Keywords: mineralocorticoid pressure levels